-4(7)+2(-9)-7(-9)=z

Simple and best practice solution for -4(7)+2(-9)-7(-9)=z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(7)+2(-9)-7(-9)=z equation:


Simplifying
-4(7) + 2(-9) + -7(-9) = z

Multiply -4 * 7
-28 + 2(-9) + -7(-9) = z

Multiply 2 * -9
-28 + -18 + -7(-9) = z

Multiply -7 * -9
-28 + -18 + 63 = z

Combine like terms: -28 + -18 = -46
-46 + 63 = z

Combine like terms: -46 + 63 = 17
17 = z

Solving
17 = z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-1z' to each side of the equation.
17 + -1z = z + -1z

Combine like terms: z + -1z = 0
17 + -1z = 0

Add '-17' to each side of the equation.
17 + -17 + -1z = 0 + -17

Combine like terms: 17 + -17 = 0
0 + -1z = 0 + -17
-1z = 0 + -17

Combine like terms: 0 + -17 = -17
-1z = -17

Divide each side by '-1'.
z = 17

Simplifying
z = 17

See similar equations:

| 3*4/5 | | (x-4)(x^2-7x+2)= | | m+3m+4m+4= | | 2/6*3/4 | | 44-5h=6h | | X=20+-0.4y+-0.02z | | 9x-3(x-8)=6(x-3)+6 | | 20000(.06x+.07y)=1300 | | 9x-3(x-8)=6x-24 | | 13q-2=-28 | | 6-2x=4(2-3x)+8x | | 9=-2m+-1 | | .93x+.97(4-x)=3.8 | | 2(x-4)-x=3 | | (3x-3)(3x-8)= | | 1+8(-4n-2)=-39-8n | | -2/3r+2r=6/5r+12/5 | | (4x^2+1)(6x^2+7)= | | 5x-6-2x=4x+8 | | 6x+6=6x-9 | | 2/3(6x+9)=18 | | -8v=-80 | | -2(-x-8)=2x+15 | | -3(x-5)+12x=9(x+2)+12 | | 60+15=4 | | d-16=-50 | | 2(6w+8)=2(4w+24) | | (3x+5)=2(x+7) | | -6(x-8)=48 | | n+t+g+h=106 | | 162=11x+19 | | 3(x+5)+4x=-(x-5) |

Equations solver categories